Comment to "Toward an ethical turn of the technology: why Hans Jonas is not a technophobic": Simondon: um outro ponto de vista sobre a técnica - Carrara, Ozanan Vicente (2022)
Reference of the commented article:  OLIVEIRA, J. R. de. Para uma ethical turn da tecnologia: por que Hans Jonas não é um tecnofóbico. Trans/form/ação: revista de Filosofia da Unesp, v. 45, n. 2, p. 191-206, 2022. Received: 16/01/2022 - Accepted: 29/01/2022